Identification of the support needs of individuals with severe mental illness using the Supports Intensity Scale - Maribel Cruz; Ma. del Carmen Perez; Cristina Jenaro; Noelia Flores; Vanessa Vega (Revista Latino-Americana de Enfermagem, 2013)
OBJECTIVE: to characterize the intensity of the support needs of individuals with severe mental illness. METHODS: quantitative and descriptive study that applied the Supports Intensity Scale to a sample comprising 182 individuals. RESULTS: the supports intensity profile identifies groups, individuals, and areas with different needs of support relative to the domains of home living, health, community living, learning, employment, and social living. As a whole, the intensity level of support needs found was low, and the domains with greater needs were employment and social. CONCLUSIONS: identification of the intensity of support needs is helpful in planning integral care and detecting professional training needs. The support provision-centered approach, associated with the person-related outcomes perspective, has been sparsely applied to individuals with mental illness, and this represents the main contribution of the present study. In addition, this study introduces novel approaches to assessment that are both concordant and an innovation in nursing because they might provide a tool for understanding other disabilities.